ANALYSIS OF ORGANIZATIONAL COMMITMENT, CONTROL SYSTEM, USE OF INFORMATION TECHNOLOGY, AND COMMUNITY PARTICIPATION ON VILLAGE FUND MANAGEMENT ACCOUNTABILITY - Anton Sukontjo; Erawati Kartika; Sri Kushalimah (SIMAK, 2023)
The purpose of this study was to empirically examine the effect of Organizational Commitment, Control System, Utilization of Information Technology, and Community Participation on Village Fund Management Accountability. This research was conducted in the village administration in Petungkriyono District, Pekalongan Regency which consists of 9 villages. The population in this study were all village officials and the head of the Village Consultative Body (BPD). The technique used in sampling is simple random sampling, because the population is small so that the village apparatus and the head of the BPD have the same opportunity, which obtained a sample of 100 respondents. This study uses multiple linear regression as an analytical tool. Data analysis was performed using SPSS software version 23.0. Based on the results of hypothesis testing, it can be concluded that simultaneously Organizational Commitment, Control System, Utilization of Information Technology, and Community Participation have a positive and significant effect on Village Fund Management Accountability. Partial test of the four hypotheses proposed that Organizational Commitment has a positive and significant effect on Village Fund Management Accountability, Control System has no significant effect on Village Fund Management Accountability, Utilization of Information Technology has no significant effect on Management Accountability Village Funds, Community Participation have a positive and significant impact on Village Fund Management Accountability.